Effect of moderate - vigorous intensity physical exercise on female sex hormones in premenopausal university students in Nnewi, Nigeria - Atuegbu, Chidiadi M.; Meludu, Samuel C.; Dioka, Chudi E.; Onyenekwe, Charles C.; Onuegbu, Jude A.; Onah, Christian E.; Onyegbule, Onyema A.; Analike, Adanma R.; Udo, John N. (International Journal of Research in Medical Sciences, 2017)
Background: Sedentary lifestyle and diseases associated with it is on the increase in our communities, state and country as a whole. The objective was to determine the effect of exercise on ovarian reserve status of the participants using day 3 FSH, LH and estrogen values and the ovulatory status of the participants using day 21 progesterone values. Methods: The study was a prospective comparative study. A total of 30 participants were recruited for this work. They were divided into 2 groups: 15 subjects that did exercise for 1 month and 15 controls that didn’t do any form of exercise. Baseline blood samples were collected from the two groups on day 3 and day 21 of the menstrual cycle. The subjects started exercise on day 1 of the next menstrual cycle. Blood samples were collected from the subjects and control on day 3 and day 21 of the next menstrual cycle. Results:There was significant reduction in weight and therefore BMI of the study group compared to control group and study group baseline after one month of exercise (P<0.05). There were no significant differences in the baseline levels of Estrogen, FSH, LH and progesterone between the subjects and control groups before the exercise, but after 1 month of exercise, there were significant differences in the levels of estrogen, FSH, LH and progesterone in these groups (P<0.01). Among the study group there were significant differences in the baseline and final levels of Estrogen, FSH, LH and Progesterone (P<0.01). Conclusions: The hormonal pattern shows that moderate-vigorous exercise may increase the responsiveness and sensitivity of the follicles to FSH and LH with attendant increase in ovulatory status of young females.